Lateral Periodontal Cyst: a Case Report and Literature Review - Luis Felipe das Chagas e Silva de Carvalho; Celina Faig Lima; Luiz Antonio Guimarães Cabral; Adriana Aigotti Haberbeck Brandão; Janete Dias Almeida (eJournal of Oral Maxillofacial Research, 2010)
Background: The lateral periodontal cyst is considered a developmental odontogenic cyst with unusual occurrence. In most cases it is preliminary diagnosed as a radiographic finding, presenting as well circumscribed or as a round or teardrop-shaped radiolucent area. Due to its location it can easily be misdiagnosed as a lesion of endodontic origin. Final diagnosis should be based on histopatological examination. The purpose of this paper is to report a classic case of lateral periodontal cyst located in the anterior region of mandible and to review the relevant literature which describes the clinical, radiological and histopathological features of lateral periodontal cysts.Methods: A 50 years female patient complained of an asymptomatic gingival swelling in the region between the left mandibular lateral incisor and canine. Radiographic examination revealed a well circumscribed radiolucency with approximately 0.5 cm diameter with a radiopaque margin between the roots of the left mandibular lateral incisor and canine. The adjacent teeth had vital pulp.Results: A total enucleation of the lesion was performed, and intraoperative examination showed a single lesion with no communication between the cyst's cavity and the oral environment. Histological examination revealed that the lesion was “lateral periodontal cyst of developmental origin”. There was no recurrence or complications for 24 months follow-up.Conclusions: The lateral periodontal cyst can be considered in the differential diagnosis when a radioloucent lesion appears adjacent to the roots of vital teeth. The treatment of choice is surgical removal and subsequent histological evaluation to confirm the diagnosis. Relapses are infrequent.